Al Ishāri Interpretation and Models of its Applications: "Rūḥ al Ma’ānī"as Model - Al Ghananim, Enad Ghaleb Mohammad (Journal of Islamic and Religious Studies, 2022)
This research dealt with the study of the subject of "indicative interpretation" by Imam Alusi in his interpretation of "Ruh al Ma’ani", following the inductive, analytical, and inferring approach, and the study revealed the great importance given by God to his dear book, and to the scholars of the interpreters, and the study found that the indicative interpretation that does not conflict with Sharia, and is within clear controls and criteria, is acceptable to scholars, unlike what was interfered with the words of philosophers who deviated from the road in his interpretation. Alusi combined interpretation with accepted opinion, including the indicative interpretation, as well as a school in itself, and then concluded the study with the most important findings of this research.